Experimental investigation of carbonation on concrete under variable parameters - Ranjan A.; Kumar R.; Mohan D. (My University, 2025)
Durability of hardened concrete depends upon several factors. Carbonation is one of the most important factors upon which durability greatly depends. The natural process of Carbonation of concrete structures in our surroundings is very slow while accelerated carbonation effect on the concrete simulates the actual behavior of carbonation in concrete. In this study, experiments have been conducted on concrete cubes by varying multiple parameters such as type of cement, water/cement ratio, effect of super plasticizer, and curing period in order to assess the depth of carbonation. Carbonation effect on concrete has been simulated in controlled carbonation chamber in short duration of time. Phenolphthalein indicator has been used to assess carbonation depth. © IAEME Publication.